1984
DOI: 10.2307/1590128
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Aflatoxin B 1 in Chickens Given Feed Contaminated with Aspergillus flavus and Reduction of the Toxicity by Activated Charcoal and Some Chemical Agents

Abstract: Aspergillus flavus NRRL 3357 was grown on enriched long-grain rice for 7-10 days to produce aflatoxin B1 (AFB1). The quantity of AFB1 in moldy rice was determined by thin-layer chromatography using ultraviolet light. When the dried moldy rice powder was fed to day-old Hubbard X Hubbard broiler chicks in unmedicated feed (AFB1 level 10 ppm) for 8 weeks, there was a profound reduction in weight gain and feed consumption. Chickens fed AFB1 developed severe liver damage, as determined by the concentration of hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 10 publications
4
18
0
2
Order By: Relevance
“…Mortality was low but marked hepatic damage was manifested by enlarged and hemorrhagic liver (Carnaghan et al, 1966). Relatively, high dietary levels of aflatoxin B1 (0-10 ppm) given to Rock type broiler chickens have been reported to cause substantial decrease in weight gain, feed efficiency and hepatic microsomal drug metabolizing enzymes with concomitant increase in serum glutamic oxalacetic transaminase activity reflecting liver damage (Dalvi and McGowan, 1984;Dalvi and Ademoyero, 1984). Metabolic alterations caused by aflatoxins in chickens result in elevated lipid levels (Tung et al, 1972;Donaldson et al, 1972), disruptions in hepatic protein synthesis (Tung et al,1975) which result in several blood coagulation disorders (Doerr et al,1976;Bababunmi and Bassir, 1982), immunosuppression and decreased plasma amino acid concentrations (Voight et al, 1980).…”
Section: Chickensmentioning
confidence: 99%
“…Mortality was low but marked hepatic damage was manifested by enlarged and hemorrhagic liver (Carnaghan et al, 1966). Relatively, high dietary levels of aflatoxin B1 (0-10 ppm) given to Rock type broiler chickens have been reported to cause substantial decrease in weight gain, feed efficiency and hepatic microsomal drug metabolizing enzymes with concomitant increase in serum glutamic oxalacetic transaminase activity reflecting liver damage (Dalvi and McGowan, 1984;Dalvi and Ademoyero, 1984). Metabolic alterations caused by aflatoxins in chickens result in elevated lipid levels (Tung et al, 1972;Donaldson et al, 1972), disruptions in hepatic protein synthesis (Tung et al,1975) which result in several blood coagulation disorders (Doerr et al,1976;Bababunmi and Bassir, 1982), immunosuppression and decreased plasma amino acid concentrations (Voight et al, 1980).…”
Section: Chickensmentioning
confidence: 99%
“…The results from the present study are not in agreement with other studies where significantly reduced body weights were observed when birds were exposed to higher dietary AF (400 and 600 ppb AF). The depression in growth upon feeding AF was attributed to reduced protein and energy utilization (Smith and Hamilton, 1970;Lanza et al 1980;Doerr et al, 1983;Dalvi and Ademoyero, 1984;Verma et al, 2002) which impaired nutrient absorption and reduced pancreatic digestive enzyme production (Osborne and Hamilton, 1981) and consequently reduced appetite (Sharline et al, 1980). Similarly, significant depressions in body weight gain were also recorded in broilers given diets containing 1 and 2 mg/kg of AF (1000 to 2000 ppb) at 4 and 7 weeks of age.…”
Section: Growth Performancementioning
confidence: 99%
“…The larger problem is contaminated animal products that potentially threat the public health. Therefore, the toxin must be determined by analysis in feeds (8). Although, there are some difference according to country and regions, most dangerous mycotoxins in poultry feeds are aflatoxins (AFL) produced by Aspergillus, ochratoxin A (OTA) produced by Penicillium and Aspergillus spp and deoxynivalenole (DON), zearalenone (ZEA), T-2 toxin and fumonisin (FUM) produced by Fusarium (6,16).…”
Section: Introductionmentioning
confidence: 99%